MEMAHAMI MOTIF PERKAWINAN BIDADARI DENGAN LAKI-LAKI BUMI SEBAGAI SPIRIT FEMINISME DALAM FOLKLORE INDONESIA - Wiyatmi, Wiyatmi (Diksi, 2021)
(Title: The Poetry's Potencies As Emotion Therapy Media in Society 5.0). This study aims to describe the function of poetry as a medium for emotional therapy in society 5.0. The data from this study are poetry texts written by students. Data were collected through test techniques (poetry writing) and non-tests (interviews, observations, and documentation). Based on the results of the study, it is said that aside from being a medium for brainstorming one's thoughts, feelings and experiences, poetry has the potential to become a medium for emotional therapy. Dictionaries, Enjambments, typography, and arrangement of lines can be said to represent the soul of the poet when angry, happy, in love, traumatized, experiencing sadness, and other emotions. The entire contents of the poem is a reflection of the emotions that the poet naturally experienced, saw, and felt in the packaging of words that were solid and full of meaning. Keywords: poetry, emotion therapy, therapy media, society 5.0 (Title: Understanding The Motif of Midwifery With Earth Men as The Spirit of Feminism in the Indonesian Folklore). Folklore is one of the intellectual works that was born as an expression of the world view of the supporting community. One of the folklore motifs found in a number of ethnic groups in Indonesia is that which tells about the marriage between earth men and angels from heaven. Among these folklore are Jaka Tarub (Java), Putri Surga (Papua), Cerita Air Tukang (Maluku), Betawol (Miraculous North Kalimantan), Malim Deman and Puti Bungsu (Riau), Tomanurun (Toraja), and Si Lanang and Punai (South Kalimantan). This study tries to compare and understand the motif of marriage between men of the earth and deities by using the perspective of feminism. The results showed that the deities had higher positions and abilities than men of the earth who married him. This means that the upper world (heaven or heaven) the place of origin of the deities in social stratification is considered higher than the underworld, even though the two complement each other. The existence of the motif of marriage between men of the earth and desities found in a number of ethnic groups in Indonesia shows a high appreciation for the figure of the mother as an ancestor who inherited certain ethnicities, which is a manifestation of the spirit of feminism in a number of folklores in Indonesia. Keywords: deities, world above, world below, feminism